Biomimetic surface functionalization of clinically relevant metals used as orthopaedic and dental implants. (22nd November 2017) - García-Gareta, Elena; Hua, Jia; Orera, Alodia; Kohli, Nupur; Knowles, Jonathan C; Blunn, Gordon W
Abstract: Titanium and its alloys or tantalum (Ta) are materials used in orthopaedic and dental implants due to their excellent mechanical properties and biocompatibility. However, their bioactivity and osteoconductivity is low. With a view to improving the bioactivity of these materials we hypothesised that the surface of Ta and TiAl6V4 can be functionalised with biomimetic, amorphous nano-sized calcium phosphate (CaP) apatite-like deposits, instead of creating uniform coatings, which can lead to flaking, delamination and poor adherence. We used Ta and TiAl6V4 metal discs with smooth and rough surfaces. Amorphous CaP apatite-like particles were deposited on the different surfaces by a biomimetic rapid two-step soaking method using concentrated simulated body fluid (SBF) solutions without a pre-treatment of the metal surfaces to induce CaP deposition. Immersion times in the second SBF solution of 48 and 18 h for Ta and TiAl6V4 respectively produced CaP deposits composed of amorphous globular nano-sized particles that also contained Mg, C and O. Longer immersion times produced more uniform coatings as well as an undesired calcite mineral phase. Prediction of in vivo behaviour by immersion in regular SBF showed that the obtained CaP deposits would act as a catalyst to rapidly form a Ca deficient CaP layer that also incorporates Mg. The amorphous CaP apatite-like deposits promoted initial attachment, proliferation and osteogenic differentiation of bone marrow derived mesenchymal stem cells. Finally, we used our method to functionalise 3D porous structures of titanium alloy made by selective laser sintering. Our study uses a novel and cost-effective approach to functionalise clinically relevant metal surfaces in order to increase the bioactivity of these materials, which could improve their clinical performance.